Minimizing sulfide oxidation on acid sulfate farmlands by enhanced controlled drainage and subsurface irrigation - Österholm, P.; Virtanen, S.; Uusi-Kämppä; Rosendahl, R.; Westberg, V.; Mäensivu, M.; Ylivainio, Kari; Yli-Halla, Markku; Turtola, Eila (eng, 2012)
http://ojs.tsv.fi/index.php/AFS/article/view/6510/5540
Keywords: Ka; sulfaattimaat; sulfidit; salaojitus; pohjavesi; acid sulfate soils; sulphides; groundwater; subsurface drainage; oxidation